Quantitative gender analysis country report, Burundi: Building equitable climate resilient African bean and insect sectors - Hakizimana, Marie Bernadette; Ndabashinze, Blaise; Ouya, Frederick; Lutomia, Cosmas; Ketema, Dessalegn; Nchanji, Eileen (Bioversity International and International Center for Tropical Agriculture, 2025)
Agriculture remains key to livelihoods, food and nutrition security, and economic resilience in Burundi, where smallholder farmers rely largely on rain-fed production systems dominated by food crops (beans and sorghum) and fruit trees. However, the agriculture sector is currently facing rising weather- and climate-related difficulties, including protracted dry spells, irregular rainfall, and weather-induced production hazards that affect agricultural output, income stability, and household resilience. These climatic risks intersect with institutional and gender inequities, such as unequal access to land, credit, extension services, agro-weather information, and market opportunities, which notably hinder women and youth farmers. As Burundi advances climate-resilient and inclusive agricultural development, understanding gender-differentiated engagement, decision-making, and benefit-sharing across these value chains is crucial for achieving equitable resilience results. This quantitative study analyses the participation, resource access, market engagement, and climate information use of men and women farmers throughout the common bean, fruit tree, and insect value chains in the northern districts of Kirundo, Ngozi, and Muyinga. Findings demonstrate continuing gender differences in landholding, group participation, enterprise management, market control, and intra-household decision-making. Although women contribute substantially to agricultural labour, particularly in planting, harvesting, processing, and community-based financial groups, men retain greater control over land, input use, production decisions, and income from high-value enterprises. In bean production, men are more likely to determine varietal choices and control marketing and income use, while women emphasise home consumption and face greater barriers in access to extension services and market information. In fruit tree enterprises, men dominate tree management, selling, and decisions on when and where fruit is marketed, including greater engagement in export-oriented and commercial channels, whereas women are more concentrated in local and informal markets. Participation in insect enterprises remains nascent, with men demonstrating more involvement in insect use for feed and beekeeping assets, while women have lower exposure to technical training and innovation prospects. Across all three value chains, farmers highlighted issues that limit productivity and resilience, including limited availability of quality inputs, weak pest and disease management capabilities, inadequate storage and post-harvest handling, and restricted access to financial services. Gender-specific limitations are evident: women encounter higher constraints linked to awareness, language, mobility, and extension participation, while youth face inadequate resources, asset ownership, and enterprise start-up support. Access to agro-weather and climate information services is relatively widespread, yet disparities persist in training, frequency of access, and capacity to meaningfully apply climate information, with women reporting more irregular access and lower participation in WIS-related training opportunities. These patterns underscore the interplay between climate hazards and gendered power relations, which together impede women’s and youth farmers’ ability to fully benefit from agricultural markets and climate-smart opportunities. Despite these limitations, the findings suggest opportunities to promote equitable climate resilience through gender-responsive interventions that expand training, financial inclusion, and climate-smart technology adoption across the bean, fruit tree, and insect value chains. Priority investment areas include climate-smart agronomic and pest-management training, enhanced seed and planting material systems, post-harvest and storage infrastructure, strengthened market linkages, and specialised financial and entrepreneurship support for women and youth. Enhancing access to agro-weather information services, boosting gender-inclusive extension outreach, and fostering joint household decision-making will further strengthen adaptive capacity and production. The evidence generated through this study provides a strategic foundation for the Building Equitable Climate-Resilient African Bean and Insect Sectors (BRAINS) project to design targeted, gender-responsive, and socially inclusive interventions that reduce gender gaps, strengthen household resilience, and advance equitable participation in climate-responsive agricultural enterprises.